Defensive fortifications in Cyrenaica located Outside the main Cities During the Roman Era and its Defensive role (Astudy of examples of it) (Journal of Human Sciences, 2024)
The geographical location of the state of Cerenaica played an important role in its history and civilization throughout the ages it passed through. With the death of Ptolemy Apion in 96 BC, ownership of the Ptolemaic properties in Cerenaica was transferred to the Romans. As a result of the danger posed by the local tribes, it was necessary to pay attention to the Roman defensive fortifications there, in order to impose To achieve this goal, the Romans followed a military strategy that relied on three aspects to achieve it: auxiliary military divisions, main forts, and roads. The Romanian military strategy relied on the stability of elements of the Romanian military divisions that assisted it. The Romans used the local population to form these auxiliary teams, and in this aspect, literary and archaeological sources provided important data about the stability of the elements of the auxiliary military teams in Cyrenaica. The Romans worked on constructing defensive fortifications to serve as headquarters for the soldiers of the auxiliary teams operating in Cirinaica. The Roman military strategy aimed to fortify the borders of the state, in line with the geographical division of the state. A group of watchtowers or guard towers were also erected. The Roman military planning strategy required the establishment of two types of them, the first It was built for the purpose of strengthening fort gates and walls. As for the second type, it was built in isolated areas on the Roman border and was built individually. As for the roads, the Roman interest in the road network in Cerenaica began in the middle of the first century AD. The Romans worked to improve the road system by reclaiming and maintaining it, and erecting millstones along its length to determine the distances between regions. It seems clear that the Roman road system in Cerenaica in general Simple, as it is made up of main roads linking parts of the state, its main cities, and the interior regions.